Improving Employee Performance Through Innovative Work Behavior, Tbk Periode 2011–2020 - Fauji Sanusi; Dibyantoro Dibyantoro (Syntax Literate, 2022)
The higher the level of competition in the industrial sector, it is necessary for the company's efforts to respond well to this in order to survive through internal strategies in the form of improving employee performance. Organizational culture is found to be one of the factors that can improve employee performance. The main purpose of this study is to build a model in an effort to improve employee performance involving innovative work behavior as an intervening variable for the influence of organizational culture on employee performance. The population in this study were employees of companies engaged in the manufacturing sector with 276 employees. Samples were taken 127 employees using purposive random sampling method. Structural Equation Modeling (SEM) was used to test the statistical significance of the path coefficients against the three (3) established hypotheses. The findings of the study indicate that organizational culture and innovative work behavior have a positive and significant influence on employee performance. Innovative work behavior can be an intervening variable for the influence of organizational culture on employee performance.